Sustainable supply chain performance, its practice and impact on barriers to collaboration. Issue 8 (8th August 2019) - Kumar, Gopal; Goswami, Mohit
Abstract : Purpose: Sustainable supply chain (SSC) provides one opportunity to achieve competitive advantage. To achieve SSC through triple bottom line (TBL) – economic, environment and social – is extensively discussed. Most literature in dealing with environmental issues undermine social dimension even though its potential to bring outstanding results by earning customers loyalty and commitment is immense. Local orientation and different context motivate firms to prioritize sustainability dimensions differently. The purpose of this paper is to conceptualize SSC performance as three dimensional second-order formative construct which is caused by three first-order reflective constructs. Further, the authors examined effect of sustainable performance on barriers to sustainability through collaboration. Design/methodology/approach: The model is validated by data collected from industries in India using both partial least squares and covariance based structural equation modeling. The authors find the model is valid for both manufacturing and service sectors. Findings: In Indian context, social dimension is most and environmental dimension is least important differentiating it from developed economy. The authors find sustainable performance subsequently mitigates barriers and risks to sustainability, thereby reducing its impact over time. Originality/value: This study conceptualizes SSC performance as three dimensional second-order formative construct which is caused by three first-order reflective constructs. Given criticisms to TBL for being western-centric, this study unearths insightful phenomena having implications for both developing and developed world. Further, the authors find sustainable performance reduces effects of barriers to collaboration necessary to achieve SSC. This study contributes to both theory and practice by modeling sustainability performance.